Supercomputing Frontiers: 6th Asian Conference, SCFA 2020, Singapore, February 24-27, 2020, Proceedings - Panda, Dhabaleswar K (Lecture Notes in Computer Science, 2020)
This open access book constitutes the refereed proceedings of the 6th Asian Supercomputing Conference, SCFA 2020, which was planned to be held in February 2020, but unfortunately, the physical conference was cancelled due to the COVID-19 pandemic. The 8 full papers presented in this book were carefully reviewed and selected from 22 submissions. They cover a range of topics including file systems, memory hierarchy, HPC cloud platform, container image configuration workflow, large-scale applications, and scheduling.